An Iodine-Based Starch Test to Assist in Selecting Leaves for HLB Testing - Ed Etxeberria; Pedro Gonzalez; William O. Dawson; Timothy Spann (EDIS)
HS1122, a 5-page illustrated fact sheet by Ed Etxeberria, Pedro Gonzalez, William Dawson, and Timothy Spann, presents an IFAS-developed version of a rapid, simple field diagnostic tool for Citrus Greening (Huanglongbing) and how to interpret the results. Includes references. Published by the UF Department of Horticultural Sciences, December 2007.